2019
DOI: 10.1136/fmch-2019-000202
|View full text |Cite
|
Sign up to set email alerts
|

Factors for self-assessment score of interprofessional team collaboration in community hospitals in Japan

Abstract: Objective Interprofessional collaboration is considered an important strategy in overcoming the complex issues associated with healthcare outcomes. A nationwide, community-based integrated care system developed for the care of older people in individual communities in Japan requires community hospitals to deliver integrated care to coordinate efforts for creating effective environments for health. This study aimed to explore the factors associated with the self-assessment score of interprofessional collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
(35 reference statements)
1
11
1
2
Order By: Relevance
“…was ≥0.50, which supports convergent validity. Known-group validity demonstrated the expected difference among relationships between nurses and non-nurses (Haruta et al, 2019). Overall, these validated steps warrant the value of JASSIC final version as a selfassessment tool.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…was ≥0.50, which supports convergent validity. Known-group validity demonstrated the expected difference among relationships between nurses and non-nurses (Haruta et al, 2019). Overall, these validated steps warrant the value of JASSIC final version as a selfassessment tool.…”
Section: Discussionmentioning
confidence: 74%
“…For convergent validity, the correlation between the total score of the Assessment of Interprofessional Team Collaboration Scale-II (AITCS-II) (Orchard et al, 2018), whose Japanese version was validated in a similar way to the present questionnaire (Yamamoto & Haruta, 2019), and the total score of JASSIC final version was examined using Pearson's correlation coefficient. For known-group validity, the total scores for JASSIC final version between nurses and non-nurses were analyzed with an unpaired t-test based on a previous study in Japan, which showed that the AITCS score for nurses is higher than that for other professionals (Haruta et al, 2019). Analyses were performed using IBM SPSS software (version 26) and Amos 25 Graphics.…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se que desde 2017, período no qual as ementas foram avaliadas, a comissão de organização do curso e a comissão de graduação têm a proposta e iniciativa de reorganizar as ementas de modo a melhorar as competências adquiridas nas disciplinas da graduação. Esses espaços de discussão têm potencial para servir tanto como ferramenta de aprendizagem em saúde, quanto como método de melhora do serviço e qualidade do ambiente de trabalho para a equipe de saúde 26 .…”
Section: Conclusõesunclassified
“…Research in Japan that assessed the practice of interprofessional collaboration of medical personnel in three hospitals has shown that age (i.e., younger professionals) and profession (e.g., nursing) were the most influential positive factors in creating a collaborative environment [16]. Healthcare practitioners from countries with complementary models (e.g., United States and Israel) possess more positive attitudes to interprofessional collaboration than healthcare practitioners from countries with hierarchical models (e.g., Italy, Mexico, and including Indonesia) [13,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%